The L2 motivational self system, L2 interest, and L2 anxiety: A study of motivation and gender differences in the Croatian context - Martinović Anna; Sorić Izabela (ExELL (Explorations in English Language and Linguistics))
Studies have shown that second language (L2) motivation can have an impact on L2 learning processes. The aim of this study was to investigate gender differences in L2 motivation among Croatian university students from the perspective of the L2MSS. The results indicated that females were more motivated than males to learn English, had higher levels of interest in English, while differences in L2 anxiety were somewhat ambiguous. Females also demonstrated that their L2 motivation was linked to motives related to the avoidance of negative outcomes suggesting that females are perhaps more conscientious learners compared to males. These findings point to a complex motivational state among females, which may indicate important gender-based differences in language learning.